Effect of ionic conductivity of a PVC-LiClO4 based solid polymeric electrolyte on the performance of solar cells of ITO/TiO 2/PVC-LiClO4/graphite - Rahman M.Y.A.; Salleh M.M.; Talib I.A.; Yahaya M. (2023)
This paper reports the effect of ionic conductivity of the solid polymeric electrolyte of polyvinylchloride-lithium perchlorate (PVC-LiClO4) on the performance of a solar cell of ITO/TiO2/PVC-LiClO 4/graphite. Titanium dioxide films have been used as a photoelectrochemical solar cells. The films were deposited onto a ITO-coated glass substrate by a screen printing technique. The electrolytes were prepared by solution casting. The ionic conductivity of the electrolytes was obtained with an impedance spectroscopy technique. ITO and graphite films were chosen as the front and counter electrode of the device, respectively. The graphite films were deposited onto a glass substrate by the electron-beam evaporation technique. The short-circuit current density and open-circuit voltage of the device were found to increase with increasing ionic conductivity of solid polymeric electrolyte of PVC-LiClO4. The highest short-circuit current density and open-circuit voltage were 0.94?Acm-2 and 186mV, respectively. The conversion efficiency was low. 2004 Elsevier B.V. All rights reserved.